Natural remedies for pest, disease and weed control - Egbuna, Chukwuebuka; Sawicka, Barbara (Academic Press, an imprint of Elsevier, 2020)
Natural Remedies for Pest, Disease and Weed Control presents alternative solutions in the form of eco-friendly, natural remedies. Written by senior researchers and professionals with many years of experience from diverse fields in biopesticides, the book presents scientific information on novel plant families with pesticidal properties and their formulations. It also covers chapters on microbial pest control and control of weeds by allelopathic compounds. This book will be invaluable to plant pathologists, agrochemists, plant biochemists, botanists, environmental chemists and farmers, as well as undergraduate and postgraduate students.